Geochemistry of Ordovician volcanic rocks of the Tetagouche Group of southwestern New Brunswick - Dostal, J. (Atlantic Geology, 1989)
The Lower to Middle Ordovician volcanic suite of the Tetagouche Group from the southwestern part of the Miramichi Terrane in the Woodstock-Meductic area in southwestern New Brunswick is composed of a bimodal basalt-rhyolite association. Thebasaltshave calc-alkalicchar acteris tics and were emplaced on the continental crust in a volcanic arc or back-arc environment. The rhyolites were probably derived by melting of an amphibolite-facies crust. The basalts differ from those of the Tetagouche Group from the Bathurst area which include within-plate basalts and MORB. However, they both may be part of a single Ordovician arc-back-arc system.